Gingival and alveolar hyperplastic reactive lesions: clinicopathological study of 90 cases - Pryscilla Giglio Peralles; Ana Paula Borges Viana; André Luiz da Rocha Azevedo; Fábio Ramôa Pires (Universidade Estadual de Campinas, 2015)
Hyperplastic reactive gingival/alveolar lesions are one of the most common subgroups of oral lesions, however few studies have focused their clinical and microscopic characteristics on our population. The aim of this study was to analyze the socio-demographic, clinical and microscopical features of 90 hyperplastic reactive gingival/alveolar lesions from an Oral Pathology Laboratory from Rio de Janeiro, Brazil. Inflammatory gingival hyperplasia (IGH) and pyogenic granuloma (PG) were the most common diagnosis in this group. Females on their 3rd to 4th decades of life were the predominant group affected and most cases affected the anterior portion of the oral cavity. Histopathology revealed that all cases were associated to chronic inflammatory infiltrate and vascular proliferation was prominent in PG. Epithelial alterations were also more common in PG, but mineralization showed marked affinity for peripheral cemento-ossifying fibroma (PCOF). Fibroblastic proliferation was more evident on PCOF and peripheral giant cell lesion (PGCL) and multinucleated giant cells were found exclusively on PGCL. Clinical and socio-demographic findings alone were not enough for distinguishing all lesions from this group, and our findings showed that few cases were suggestive of an evolutionary process